LO96: Syncope prognosis based on emergency department diagnosis: a prospective cohort study. (15th May 2017) - Toarta, C.; Mukarram, M.A.; Arcot, K.; Kim, S.; Gaudet, S.; Sivilotti, M.; Rowe, B.H.; Thiruganasambandamoorthy, V.
Abstract : Introduction: Relatively little is known about outcomes after disposition among syncope patients assigned various diagnostic categories during emergency department (ED) evaluation. We sought to measure the 30-day serious outcomes among 4 diagnostic groups (vasovagal, orthostatic hypotension, cardiac, other/unknown) within 30 days of the index ED visit.Methods: We prospectively enrolled adult syncope patients at six EDs and excluded patients with pre-syncope, persistent mental status changes, intoxication, seizure, and major trauma. Patient characteristics, ED management, diagnostic impression (vasovagal, orthostatic, cardiac, or other/unknown) at the end of the ED visit and physicians' confidence in assigning the etiology were collected. Serious outcomes at 30-days included: death, arrhythmia, myocardial infarction, structural heart disease, pulmonary embolism, and hemorrhage.Results: 5, 010 patients (mean age 53.4 years; 54.8% females) were enrolled; 3.5% suffered serious outcomes: deaths (0.3%), arrhythmias (1.8%), non-arrhythmic cardiac (0.5%) and non-cardiac (0.9%). The cause of syncope was determined as vasovagal among 53.3% and cardiac in 5.4% of patients. The proportion of patients with ED investigations (p<0.001) and short-term serious outcomes increased (p<0.01) increased in each diagnostic category in the following order: vasovagal, orthostatic hypotension, other/unknown cause and cardiac. No deaths occurred in patients with vasovagal syncope. A higher proportion of all serious outcomes occurred among patients suspected of cardiac syncope in the ED (p<0.01). Confidence was highest among physicians for a vasovagal syncope diagnosis and lowest when the cause was other/unknown.Conclusion: Short-term serious outcomes strongly correlated with the etiology assigned in the ED visit. The physician's clinical judgment should be incorporated in risk-stratification for prognostication and safe management of ED syncope patients.